2015
DOI: 10.1016/j.jcpo.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual minority experiences of cancer care: A systematic review

Abstract: a b s t r a c tThere is a lack of published evidence from within the UK examining the needs of LGB cancer patients. A full systematic review of the worldwide literature was carried out with the aim to ascertain the experiences of sexual minority cancer patients and identify specific needs required.Key databases were searched with a variety of terms relating to the sexual minority cancer experience. Suitable literature was reviewed and references within all articles were search to ensure as inclusive a review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
0
24
0
2
Order By: Relevance
“…LGBTI people feared negative consequences such as being treated as different or as 'other' whilst accessing (or attempting to access) health care. 11,40 Due to the effects of discrimination and stigma, research reported that specialist mental health or psychological support services for LGBTI people where they could make meaning of adversity were lacking. [2][3][4]11,12 Rapid reviews were consistent with wider academic literature in reporting that gay, bisexual and trans people can be deterred from accessing health care such as seeking HIV testing and treatment if they feared discrimination or encountering the stigmatizing attitudes of health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LGBTI people feared negative consequences such as being treated as different or as 'other' whilst accessing (or attempting to access) health care. 11,40 Due to the effects of discrimination and stigma, research reported that specialist mental health or psychological support services for LGBTI people where they could make meaning of adversity were lacking. [2][3][4]11,12 Rapid reviews were consistent with wider academic literature in reporting that gay, bisexual and trans people can be deterred from accessing health care such as seeking HIV testing and treatment if they feared discrimination or encountering the stigmatizing attitudes of health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…LGB people who survived cancer may benefit from additional support post-treatment to help them regain a sense of well-being. 9,11 A review of trans health needs indicated that across global health-care settings, trans people experienced significant health inequalities with higher rates of HIV and other STIs, mental distress, substance use and experiences of abuse (violence and discrimination) compared with non-trans or cisgender people. 2 In relation to mental health, research suggests that LGBT people are at higher risk of poor mental health compared to the general population with the incidence of suicidal ideation, anxiety and deliberate self-harm markedly raised.…”
Section: Thosementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, detailed information on the sexual orientation of participants was not available. Given that quality of life effects of cancer-including on sexual outcomesmay be influenced by patients' sexual orientation [36][37][38][39], future studies could examine whether the associations reported here are found for survivors of differing sexual orientation.…”
Section: Discussionmentioning
confidence: 97%
“…9 In addition, many sexual minority cancer survivors experience discrimination, gaps in care, insufficient social support, and increased social isolation. 10 Patient centeredness is a fundamental feature of quality healthcare and an important aspect of high-quality oncology care. 11,12 Central to patient-centered care is a meaningful engagement with patients and their families by healthcare providers to coordinate treatment and survivorship plans that are considerate of an individual's medical, social, and cultural needs.…”
Section: Introductionmentioning
confidence: 99%